2020
DOI: 10.1021/acsami.0c12275
|View full text |Cite
|
Sign up to set email alerts
|

Better Together: Ilmenite/Hematite Junctions for Photoelectrochemical Water Oxidation

Abstract: Hematite (α-Fe2O3) is an earth-abundant indirect n-type semiconductor displaying a band gap of about 2.2 eV, useful for collecting a large fraction of visible photons, with frontier energy levels suitably aligned for carrying out the photoelectrochemical water oxidation reaction under basic conditions. The modification of hematite mesoporous thin-film photoanodes with Ti­(IV), as well as their functionalization with an oxygen-evolving catalyst, leads to a 6-fold increase in photocurrent density with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…Instead, the broad photoinduced absorption signals peaking at % 650-700 nm were assigned to photogenerated holes. [20,53,54] In this case,t he study of photohole dynamics could be conducted [d] 3ps(Fe 4+ lifetime) [47] [a] Thin film, TF. [b] TASa fter 20 ps is comparable to steady-state thermal differencespectrum.…”
Section: Charge Carrier Dynamics For the Surface Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the broad photoinduced absorption signals peaking at % 650-700 nm were assigned to photogenerated holes. [20,53,54] In this case,t he study of photohole dynamics could be conducted [d] 3ps(Fe 4+ lifetime) [47] [a] Thin film, TF. [b] TASa fter 20 ps is comparable to steady-state thermal differencespectrum.…”
Section: Charge Carrier Dynamics For the Surface Reactionmentioning
confidence: 99%
“…We note that later investigations updated the assignment of the 580 nm absorption feature to hole trapping processes in the intraband states (located a few hundred millivolts below the conduction band). Instead, the broad photoinduced absorption signals peaking at ≈650–700 nm were assigned to photogenerated holes [20, 53, 54] . In this case, the study of photohole dynamics could be conducted without interference of electron/hole trapping processes in these intraband states.…”
Section: Charge Carrier Dynamics For the Surface Reactionmentioning
confidence: 99%
“…102 Recently, Berardi et al also reported the fabrication of the FeTiO 3 overlayer passivated hematite photoanode (FeTiO 3 / Fe 2 O 3 ) through a simple electrophoretic method. 103 In that study, the FeTiO 3 phase was confirmed by X-ray absorption fine structure (XAFS) and HRTEM with electron energy loss spectroscopy (EELS). It existed in the near-surface region and could passivate the deep surface traps and induce a large density of donor levels, leading to a strong depletion field for the facilitated charge separation and injection into the electrolyte.…”
Section: Other Positive Effects Of Ti-based Modificationsmentioning
confidence: 92%
“…Instead, the broad photoinduced absorption signals peaking at % 650-700 nm were assigned to photogenerated holes. [20,53,54] In this case,t he study of photohole dynamics could be conducted Fe L-edge EELS [d] 3ps(Fe 4+ lifetime) [47] [a] Thin film, TF. [b] TASa fter 20 ps is comparable to steady-state thermal differencespectrum.…”
Section: Charge Carrier Dynamics For the Surface Reactionmentioning
confidence: 99%